Pengembangan Media Powerpoint Interaktif Berbasis Wordwall pada Pembelajaran IPS - Sherina, Sherina; Valen, Andri; Rosalina, Elya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop a valid, practical, and effective interactive PowerPoint presentation based on Wordwall for fourth-grade social studies at SDN 44 Lubuklinggau. The research method used was Research and Development with the ADDIE development model. The results showed that the validity of the interactive PowerPoint presentation based on Wordwall for economic activities in Indonesia using Aiken's V showed a score of 0.98 from the language validator, 0.86 from the media validator, and 0.92 from the material validator, meeting the validity criteria. Analysis of the teacher and student practicality assessment sheets showed that the interactive PowerPoint presentation based on Wordwall met the criteria for very practical with an average score of 88%. Furthermore, the effectiveness assessment obtained an average N-Gain score of 0.76, categorized as high. Based on the results of the study, it can be concluded that the interactive PowerPoint presentation based on Wordwall is valid, practical, and effective, making it suitable for use in Chapter 8 on economic activities in Indonesia at fourth-grade SDN 44 Lubuklinggau. Keywords: Development; Interactive PowerPoint Presentation; Wordwall ; Social Studies; Elementary School